Plantas útiles del bosque seco tropical de la Hacienda Gascoña, Tolima (2020)
Tropical dry forest (TDF) is an ecosystem of great importance around the world, but it's currently threatened and close to disappearing. Along with biological diversity loss, knowledge and use value of plants native to this ecosystem are at risk. In search of strategies to protect the forest without forfeiting productivity, farm Hacienda Gascoña (Municipality of Piedras, Tolima) plans to carry future sustainable land management projects with the intention to restore the gallery forest. To achieve this objective different plants were registered in a field trip inside the forest and around the farm. This research reviewed the use value of these plants and their phytochemical potential, conservation status, origin, and endemism. A total of 74 individuals were registered, from which 55 were reported down to species. The use value of these species were mostly registered as human medicine, timber, and ornamental. One endemic species was identified (Senegalia affinis), two species were found to be near threatened (Bursera graveolens and Anacardium excelsum), and two species in threat: one was reported in danger (Vanilla pompona), and the other in critical danger (Swietenia macrophylla). Furthermore, Momordica charantia had the highest number of pharmacological uses, which implies a great potential to be used in future research. The relevance of this study relies on knowing the applications of species that live near and inside TDF to develop future sustainable projects that includes forest and species protection that are found in danger.